SNP/haplotype associations in cytokine and cytokine receptor genes and immunity to rubella vaccine - Dhiman, Neelam (2010)
An effective immune response to vaccination is, in part, a complex interaction of alleles of multiple genes regulating cytokine networks. We conducted a genotyping study of Th1/Th2/inflammatory cytokines/cytokine receptors in healthy children (n=738, 11–19 years) to determine associations between individual single-nucleotide polymorphisms (SNPs)/haplotypes and immune outcomes after two doses of rubella vaccine. SNPs (n=501) were selected using the ldSelect-approach and genotyped using Illumina GoldenGate(™) and TaqMan assays. Rubella-IgG levels were measured by immunoassay and secreted cytokines by ELISA. Linear regression and post hoc haplotype analyses were used to determine associations between single SNPs/haplotypes and immune outcomes. Increased carriage of minor alleles for the promoter SNPs (rs2844482 and rs2857708) of the TNFA gene were associated with dose-related increases in rubella antibodies. IL-6 secretion was co-directionally associated (p≤0.01) with five intronic SNPs in the TNFRSF1B gene in an allele dose-related manner, while five promoter/intronic SNPs in the IL12B gene were associated with variations in IL-6 secretion. TNFA haplotype AAACGGGGC (t-statistic=3.32) and IL12B promoter haplotype TAG (t-statistic=2.66) were associated with higher levels of (p≤0.01) rubella-IgG and IL-6 secretion, respectively. We identified individual SNPs/haplotypes in TNFA/TNFRSF1B and IL12B genes that appear to modulate immunity to rubella vaccination. Identification of such “genetic fingerprints” may predict the outcome of vaccine response and inform new vaccine strategies.